The Impact of Tax Scrutiny on Cryptocurrency Investor Behavior: A Qualitative Synthesis of Tax-Loss Harvesting and Wash Trading Strategies - Yessica Amelia; Ngadi Permana (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review investigates how tax scrutiny influences investor behavior in the cryptocurrency market, with a focus on tax-loss harvesting and wash trading strategies. As governments enhance transparency and enforcement, crypto investors increasingly adapt their behaviors to optimize after-tax outcomes. The review synthesizes recent academic findings that highlight the growing use of legal tax-loss harvesting and the controversial persistence of wash trading, particularly in unregulated exchanges. Evidence suggests that regulatory uncertainty and inconsistent tax treatment across jurisdictions drive strategic investor responses and, in some cases, unintended compliance gaps. This study underscores the need for updated tax frameworks capable of addressing the unique characteristics of digital assets. The analysis contributes to the broader discourse on how taxation shapes market behavior in emerging financial ecosystems